(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article touches on the topic of how fiction affects the education of the culture of behavior of older preschool children. Listening to the work, the child gets acquainted with the surrounding life, nature and the work of people. The artistic word affects not only the consciousness, but also the feelings and actions of the child.